1967
DOI: 10.1128/jb.93.5.1551-1558.1967
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l -Methionine and S -Adenosylmethionine on Growth of an Adenine Mutant of Saccharomyces cerevisiae

Abstract: methionine (SAM), in quantities up to 3 Amoles per 100 ml of medium, as equivalent sources of purine for cell growth, but not methylthioadenosine or S-adenosylhomocysteine. Utilization of SAM for growth was inhibited by the presence of L-methionine in quantities greater than 0.6 ,mole per 100 ml of medium. However, 6 ,umoles of L-methionine had no effect on growth when adenine or hypoxanthine was the source of purine. These sources also reversed the inhibitory effects of 6 ,umoles of the amino acid on the util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
(4 reference statements)
1
13
0
Order By: Relevance
“…However, S-adenosyl-D-homocysteine, in contrast to S-adenosyl-D-methionine, is taken up at a much lower rate. The rapid assimilation of S-adenosyl-L-homocysteine is in agreement with earlier observations on other strains of S. cerevisiae (4,22). S-adenosyl-L-homocysteine was degraded very fast, and no conclusion could be drawn concerning its penetration into the vacuole.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, S-adenosyl-D-homocysteine, in contrast to S-adenosyl-D-methionine, is taken up at a much lower rate. The rapid assimilation of S-adenosyl-L-homocysteine is in agreement with earlier observations on other strains of S. cerevisiae (4,22). S-adenosyl-L-homocysteine was degraded very fast, and no conclusion could be drawn concerning its penetration into the vacuole.…”
Section: Discussionsupporting
confidence: 89%
“…The examination of C. utilis in this respect was disappointing; the uptake and accumulation remained low (12). More encouraging results were obtained with Saccharomyces cerevisiae by Yall (4,22) and by Spence (5,18) and their co-workers who studied several features of the specificity and mechanism of active transport by the cytoplasmic membrane. It was not possible, however, to draw conclusions on the intracellular distribution or accumulation of the material in the vacuole, because the level remained too low to permit conclusive ultraviolet micrography.…”
mentioning
confidence: 99%
“…In the presence of excess L-methionine, there is a large accumulation of S-AM in yeast (10,11). Since ATP is required for the conversion (2), previous investigators have suggested that depletion of the intracellular ATP pool due to overproduction of S-AM causes the observed inhibition (5,(13)(14)(15). Thus far, however, no direct evidence has been presented showing that the ATP pool is depleted.…”
mentioning
confidence: 99%
“…Determinations of pH were made with a pH meter (Leeds and Northrup Co., Philadelphia, Pa.). Radioactive assays were made in a Tri-Carb liquid scintillation counting system (model 314 (Packard Instrument Co., Downers Grove, Ill.)), using techniques that have been described (10). All counts were corrected for decay.…”
Section: Methodsmentioning
confidence: 99%